Correlation Analysis of Ocular Symptoms and Signs in Patients with Dry Eye - Hang Song; Mingzhou Zhang; Xiaodan Hu; Kaixiu Li; Xiaodan Jiang; Yan Liu; Huibin Lv; Xuemin Li (Journal of Ophthalmology, 2017)
Purpose. To analyze the correlations between the ocular surface signs and symptoms in patients with dry eye. Methods. In this observational study, 176 dry eye patients, including 60 males and 116 females, were enrolled and their dry eye symptoms and ocular signs were observed. Partial correlation analysis was conducted between OSDI score and each ocular surface sign, and the correlations were further discussed in different age groups. Then multiple linear regression analysis was used to further explore the influence of these signs on OSDI score. Results. Our correlation analyses showed that rounding of lid margins, notching of lid margins, vascularity of lid margins, hyperkeratinization, plugging of orifices, main duct dropout, and conjunctival congestion all had a positive correlation with OSDI score, while main duct number (central 1 cm) and BUT had a negative one. Further analysis suggested that these correlations varied in different age groups. Multiple linear regression analysis indicated that main duct number (central 1 cm), rounding of lid margins, and hyperkeratinization significantly affected OSDI score. Conclusions. Close attention should be paid to the morphology and structure of the eyelid margin and the function of meibomian gland in the diagnosis, treatment, and follow-up of dry eye diseases.